2018
DOI: 10.15252/emmm.201708289
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor efficacy of a novel CLK inhibitor via targeting RNA splicing and MYC‐dependent vulnerability

Abstract: The modulation of pre‐mRNA splicing is proposed as an attractive anti‐neoplastic strategy, especially for the cancers that exhibit aberrant pre‐mRNA splicing. Here, we discovered that T‐025 functions as an orally available and potent inhibitor of Cdc2‐like kinases (CLKs), evolutionally conserved kinases that facilitate exon recognition in the splicing machinery. Treatment with T‐025 reduced CLK‐dependent phosphorylation, resulting in the induction of skipped exons, cell death, and growth suppression in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 55 publications
(76 reference statements)
4
89
0
Order By: Relevance
“…Identification of other genes/mRNA commonly regulated by CLK2 and MYC may help to understand the CLK inhibition vulnerability upon MYC induction. In fact, Iwai et al () only establish a clear correlation between both MYC amplification and a high expression of CLK2 in BCa, suggesting that a significant heterogeneity exists among tumor types in terms of molecular mechanistics. Hematological cancers also seem to benefit from CLK2 inhibition, although CLK2 or MYC did not sensitize these cells to T‐025, thus indicating that alternative mechanisms account for such effects.…”
Section: Overview Of As Modulation By Clk2 Myc and The T‐015 Inhibitormentioning
confidence: 99%
See 3 more Smart Citations
“…Identification of other genes/mRNA commonly regulated by CLK2 and MYC may help to understand the CLK inhibition vulnerability upon MYC induction. In fact, Iwai et al () only establish a clear correlation between both MYC amplification and a high expression of CLK2 in BCa, suggesting that a significant heterogeneity exists among tumor types in terms of molecular mechanistics. Hematological cancers also seem to benefit from CLK2 inhibition, although CLK2 or MYC did not sensitize these cells to T‐025, thus indicating that alternative mechanisms account for such effects.…”
Section: Overview Of As Modulation By Clk2 Myc and The T‐015 Inhibitormentioning
confidence: 99%
“…While Iwai et al () showed that T‐025 also inhibited DYRK1A, a kinase that has been postulated as a tumor suppressor in some cancers (Liu et al , ), they point out that DYRK1A depletion in cancer cells blunt T‐025 treatment effects. Moreover, response sensitivity to T‐025 treatment did not correlate with DYRK1A expression levels, implying that T‐025 acts mainly through CLK2 inhibition.…”
Section: Overview Of As Modulation By Clk2 Myc and The T‐015 Inhibitormentioning
confidence: 99%
See 2 more Smart Citations
“…In PCa and other malignancies, mutations in genes coding for 63RBPs and changes in their expression levels have been observed 11,16 . Moreover, AS appears to 64 represent a cancer therapeutic vulnerability in leukaemia and breast cancer driven by the oncogenic 65 TF MYC [17][18][19] . MYC has also been shown to transcriptionally regulate expression of AS-associated 66 RBPs in lymphoma, lung cancer and glioma pre-clinical models 20-22 .…”
mentioning
confidence: 99%